2004
DOI: 10.1183/09031936.04.00060304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in utero growth retardation on lung function at follow-up of prematurely born infants

Abstract: Effect of in utero growth retardation on lung function at follow-up of prematurely born infants. A. Greenough, B. Yuksel, P. Cheeseman. #ERS Journals Ltd 2004. ABSTRACT: The aim of the study was to determine if prematurely born children who had suffered intra-uterine growth retardation (IUGR) had more severe lung function abnormalities than those born an appropriate weight for gestational age (AGA).Analysis of the lung function results of 119 infants (median (range) gestational age of 30 (23-35) weeks) was und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 19 publications
0
67
0
4
Order By: Relevance
“…Adjustment for size at birth is important, as we 20 and others have shown that intrauterine growth retardation adversely effects infant lung function; in particular, airways resistance is significantly related to intrauterine growth retardation. Results of previous studies 3 21-26 are consistent with diminished airway function in male compared with female infants and children.…”
Section: Discussionmentioning
confidence: 99%
“…Adjustment for size at birth is important, as we 20 and others have shown that intrauterine growth retardation adversely effects infant lung function; in particular, airways resistance is significantly related to intrauterine growth retardation. Results of previous studies 3 21-26 are consistent with diminished airway function in male compared with female infants and children.…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine growth restriction (IUGR) is a significant complication of pregnancy associated with increased risks of perinatal mortality and morbidity, including compromised lung development such as respiratory distress syndrome (7) and long-term impaired lung function in children (8) and adults (9). In experimental studies, structural changes in the IUGR fetal lung have been reported that may underlie impaired lung function.…”
mentioning
confidence: 99%
“…5 FRC pleth includes the volume of any gas trapped behind obstructed airways. Plethysmography has been used by numerous research groups since the 1960s, [6][7][8][9][10][11][12][13] and guidelinesfor standardizingequipment and techniqueswere publishedrecently. 5 Commerciallyproducedinfantplethysmographs that adhere to most of these specifications, and which have FDA and the Communauté Européene (CE) certificat, are now available.…”
Section: Which Methods and Equipment Can Be Used For Clinical Or Resementioning
confidence: 99%